2017
DOI: 10.26656/fr.2017.2(2).260
|View full text |Cite
|
Sign up to set email alerts
|

Sensory evaluation of ice cream with hydrosoluble soy extract

Abstract: Ice cream is a nutritious food because it contains ingredients responsible for supplying energy to the body. Soy has a high nutritional value and functional properties which make it to be an alternative ingredient to replace cow's milk. The purpose of this paper was to formulate an ice cream with hydrosoluble soy extract and submitted to a sensory evaluation. Two formulations of ice cream were prepared: one soy-based and the other with cow's milk (control). Both ice creams were submitted to a sensory evaluatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
0
4
0
1
Order By: Relevance
“…Soy products commonly exhibit resistance among consumers because of their characteristic taste. Bueno et al (2018) developed ice cream based on soymilk, achieving on global acceptance in sensorial analysis the value 7.6 and 6.1 to flavor, similar values to the product based on soybean developed in this work. Valim et al (2003) in work on beverage formulated with orange juice and soymilk reported that among the formulations tested, the highest grade for acceptability was 7.2.…”
Section: Resultsmentioning
confidence: 54%
“…Soy products commonly exhibit resistance among consumers because of their characteristic taste. Bueno et al (2018) developed ice cream based on soymilk, achieving on global acceptance in sensorial analysis the value 7.6 and 6.1 to flavor, similar values to the product based on soybean developed in this work. Valim et al (2003) in work on beverage formulated with orange juice and soymilk reported that among the formulations tested, the highest grade for acceptability was 7.2.…”
Section: Resultsmentioning
confidence: 54%
“…Ressaltando que todos intolerantes à lactose e vegetarianos disseram que comprariam o produto. Bueno et al (2018), ao elaborar sorvetes à base de extrato de soja, verificaram que, a partir da análise sensorial e comparação com sorvete de mesmo sabor preparado com leite, 68% dos avaliadores preferiram sorvete à base de leite do que à base de soja (32%). Apesar do índice baixo de aceitação, os autores concluíram que pode ser um bom resultado, uma vez que relacionado a um produto fabricado com soja.…”
Section: Resultsunclassified
“…For example, the literature has shown that the beany flavor of soy protein had a slightly negative effect on sensory perception; however, there was an overall positive influence on ice cream after adding soy protein. 90,91 Soy protein enhanced the physicochemical properties of the ice cream, such as the viscosity of the mix and the meltdown resistance. 17,88,92,93 Additionally, using soy extract instead of skim milk powder resulted in tiny ice crystals and reduced ice recrystallization in the ice cream.…”
Section: Acs Foodmentioning
confidence: 99%
“…Several functionalities of soy protein, such as its solubility, water-holding capacity, and emulsifying and foaming properties, enable it to be suitable for ice cream application, and many research can be found using soy protein in ice cream. For example, the literature has shown that the beany flavor of soy protein had a slightly negative effect on sensory perception; however, there was an overall positive influence on ice cream after adding soy protein. , Soy protein enhanced the physicochemical properties of the ice cream, such as the viscosity of the mix and the meltdown resistance. ,,, Additionally, using soy extract instead of skim milk powder resulted in tiny ice crystals and reduced ice recrystallization in the ice cream …”
Section: Plant-based Dairy Alternatives For Ice Cream Applicationmentioning
confidence: 99%